Data associated with, "Methane emissions from gathering and boosting compressor stations in the U.S. Supporting volume 2: Compressor engine exhaust measurements - Zimmerle, Daniel; Vaughn, Timothy; Luck, Ben; Lauderdale, Terri; Keen, Kindal; Harrison, Matt; Allen, David; Marchese, Anthony; Williams, Laurie (Colorado State University. Libraries, 2019)
The in-stack tracer method was used during the field campaign to measure unburned methane entrained in the exhaust of natural gas compressor engines ("combustion slip"). Combustion slipwas estimated by injecting a tracer gas into the exhaust stream at a known flow-rate and measuring concentrations of both the tracer gas and methane at the exhaust stack exit. The total exhaustflow was estimated from the diluted tracer gas concentration measured at the exhaust stack exit.
Authors are from: Energy Institute at Colorado State University, AECOM, SLR International Corporation, Department of Mechanical Engineering at Colorado State University, Fort Lewis College, and University of Texas, Austin, TX, USA.
Data associated with compressor engine exhaust study.
Energy Institute
Keywords: methane; emission factors; exhaust; tracer flux